A CFD numerical simulation of particle deposition characteristics in automobile tailpipe: power abatement pathways - Zhang, Rui; Gao, Ming; Fan, Mao; Han, Zunshi; Lu, Hao (Frontiers in Energy Research, 2024)
The study of the movement of pollutants through ducts facilitates the assessment and control of ambient air quality problems (AQ). Among other things, understanding the deposition and distribution of particulate matter in elbows is important for practical engineering applications. In this study, the turbulent flow field and particle deposition in a 90° bend is investigated using RANS simulation. The RNG k-ε turbulence model was employed to calculate the airflow flow field and the discrete phase model (DPM) was used to simulate the particle phase motion. Where for the discrete phase, the Discrete Random Wander (DRW) model was considered and the deposition of particles with sizes of 1, 3, 5, 10, 20, and 40μm in the flow field was investigated separately. Grid-independent validation of the models used in the simulations was performed. The effects of inlet velocity, particle size, and direction of gravity on the flow field and particle deposition in the elbow were considered. The results show that the flow field in the bend is strongly influenced by the above parameters. Among them, the turbulent disturbance in the bend section is the most intense, with high turbulent energy value, and it is also the region with the largest energy loss. The inlet velocity is negatively correlated with the deposition rate, and the particle size is positively correlated with the deposition rate.